Foreign trade of Russia and Vietnam: modern trends and prospects of development - B. A. Anikin; O. B. Anikin; N. Q. Thyong (Управление)
The subject of this study is trade between Russia and Vietnam. The purpose of the study is to identify historical features, prevailing trends, development trends, current status and prospects for the development of international trade between the specified countries. The research method is based on the logistics function of P.F. Verhulst and consists of: 1) selecting predicted values, initial value and indicators used for forecasting; 2) calculating the indicators necessary for compiling a system of equations; 3) forming a system of equations and solving it; 4) calculating forecasted indicators; 5) building a graphical forecasting model; 6) formulating conclusions. The paper presents a historical overview of trade relations between Russia and Vietnam. The study develops a mathematical model for forecasting exports and imports of Russia and Vietnam by individual indicators until 2025. The authors perform the calculation using statistical data for the period 2011–2018. The article presents the results of calculations graphically. Based on the results of calculation the paper formulates the main directions, trends and prospects for the development of foreign trade of both countries until 2025. The results of the study can be used to teach disciplines that deal with trade issues between Russia and Vietnam. The research materials may be of interest to business companies and government agencies dealing with issues related to international trade and forecasting.